Pink Blood : Homophobic Violence in Canada - Janoff, Douglas, 1958- (Book collections on Project MUSE., 2005)
"Pink Blood is the first book to analyse homophobic violence in Canada on a national scale. Douglas Victor Janoff uses legal records, case studies, and interviews with victims, activists, and police officers from thirty cities to convey the devastating impact this violence has had on queer Canadians and on the communities they inhabit. Janoff critically examines common public perceptions and police attitudes and practices, as well as hate crime legislation and policies that, despite good intentions, are often powerless to counteract this serious and complex social problem." "Drawing from a wide range of scholarship in law, criminology, sociology, psychology, philosophy, and social work, Pink Blood is a ground-breaking work from a respected researcher and community activist."--Jacket.